Matematika Praktis: Penerapan Dalam Kehidupan Sehari-hari Anak SD - Damarasri, Dinda; Handayani, Sartika; Sofiyah, Khotna (PT. Alahyan Publisher Sukabumi, 2024)
Practical use of mathematics in the daily lives of elementary school (SD) children. Practical Mathematics is a branch of mathematics that focuses on applying mathematical concepts to solve practical problems in real life. This research aims to explore how elementary school children can apply Practical Mathematics in their daily activities. Through observations and interviews with a number of elementary school students, this study identified various situations in which children use practical mathematics skills, such as calculating pocket money, measuring cooking ingredients, reading activity schedules, and so on.